Structured Validity for a quasi-experimental research of quality. They are fulfilled 50 years of the presentation in company of the quasi-experimental designs. - Fernández, Paula; Vallejo, Guillermo; Livacic-Rojas, Pablo; Tuero, Ellián (Anales de Psicología / Annals of Psychology, 2014)
Quasi-experimental investigation is that one that has as aim test a causal hypothesis manipulating (at least) an independent variable where for logistic or ethical reasons it is not possible to assign the units of investigation at random to the groups. Due to the fact that many decisions at the social level take on the basis of the result of investigations with these characteristics, it is imperative that have an exquisite planning of the application of the treatment, of the control in the process of the investigation and of the analysis of the data. This year 2013 the quasi-experimental designs expires 50 years, and this work in an honoring to Campbell and to all the investigators who day after day contribute ideas to improve the quasi-experimental method in someone of his aspects. From the hand of a review of the quasi-experimental investigations published in a period of 11 years in three journals of psychology we distinguish some aspects that refer to the care of the method. We finished work by proposing the concept of Structured Validity, which in summary, is the thread that must follow all research to test with guarantee the hypothesis that respond to the objectives it raised, in particular, in quasi-experimental investigations.